BUILDING A SUSTAINABLE BUSINESS THROUGH SOCIAL ENTREPRENEURSHIP - Liya Yulia (Jurnal Multidisiplin Sahombu, 2023)
This research aims to explore how social entrepreneurship can be an effective strategy in building a sustainable business. With increasing awareness of social and environmental issues, social entrepreneurship offers an approach that integrates social goals with economic profits. This research uses a qualitative approach with descriptive methods. In this research, it was found that social entrepreneurship plays an important role in overcoming global challenges such as climate change, social inequality and poverty. Through an innovative and sustainable community-based approach, social entrepreneurship is able to offer effective solutions to these problems. Social entrepreneurship is successful thanks to several key factors: a clear vision and mission, innovation and creativity, a sustainable business model, strong partnerships, and a focus on social impact. Managerial and leadership skills, along with the ability to adapt and be resilient, also contribute to the effectiveness and success of implementation. The combination of these factors allows social entrepreneurship to create positive and sustainable social impact.